Hubungan Pemberian ASI Eksklusif Dengan Kejadian Tuberkulosis Paru Pada Anak - Karimah Khitami Aziz (JURNAL INFO KESEHATAN, 2018)
Growth and development in childhood need to be considered to shape future generations are healthy, intelligent and qualified. Maintenance of children's health is carried out since fetus until age of 18 years. Meanwhile, children at the age of first 5 years of life have a low immune system that is susceptible to various diseases including pulmonary TB disease. One effort to maintain maternal and child health is by giving exclusive breastfeeding. The decline in the use of exclusive breastfeeding in developing countries, especially in urban areas, is the result of socio-cultural changes in the community. Pulmonary TB is a public health problem that is one of the global commitments in the MDG’s that must be controlled. Pulmonary TB is an infectious disease caused by an infection of the Mycobacterium tuberculosis and has attacked almost one-third of the world's population. Children's pulmonary TB is a TB disease that usually attacks children aged 0-14 years. Of the 9 million new cases of TB that occur worldwide each year, an estimated 1 million (11%) of them occur in children under 15 years.